2013
DOI: 10.1038/bjc.2012.568
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic landscape of oral squamous cell carcinoma

Abstract: Background:There is relatively little methylation array data available specifically for oral squamous cell carcinoma (OSCC). This study aims to compare the DNA methylome across a large cohort of tumour/normal pairs.Methods:DNA was extracted from 44 OSCCs and paired normal mucosa. DNA methylation analysis employed the Illumina GoldenGate high-throughput array comprising 1505 CpG loci selected from 807 epigenetically regulated genes. This data was correlated with extracapsular spread (ECS), human papilloma virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 55 publications
5
72
0
Order By: Relevance
“…About one half of the identified genes (e.g., ADCYAP1, FGF3, GAS7, and KDR) also exhibited potential in our tissue samples as biomarkers of oral cancer. In a recent study, Jithesh et al 39 also employed the same array and suggested that EPHA5, GSTM2, HS3ST2, MME, MT1A, MYOD1, NPY, and PENK are potential biomarkers for detecting oral cancer, as in the present study. The only triple-hit gene among the studies of Viet et al, 10 Jithesh et al, 39 and ourselves was EPHA5.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…About one half of the identified genes (e.g., ADCYAP1, FGF3, GAS7, and KDR) also exhibited potential in our tissue samples as biomarkers of oral cancer. In a recent study, Jithesh et al 39 also employed the same array and suggested that EPHA5, GSTM2, HS3ST2, MME, MT1A, MYOD1, NPY, and PENK are potential biomarkers for detecting oral cancer, as in the present study. The only triple-hit gene among the studies of Viet et al, 10 Jithesh et al, 39 and ourselves was EPHA5.…”
supporting
confidence: 67%
“…In a recent study, Jithesh et al 39 also employed the same array and suggested that EPHA5, GSTM2, HS3ST2, MME, MT1A, MYOD1, NPY, and PENK are potential biomarkers for detecting oral cancer, as in the present study. The only triple-hit gene among the studies of Viet et al, 10 Jithesh et al, 39 and ourselves was EPHA5. In addition, Nagata et al 40 reported that the aberrant methylation of a combination of ECAD, TMEFF2, RARb, and MGMT from rinse samples can detect OSCC with a sensitivity and specificity of >90% by using noninvasive methods to retrieve samples and a different methylation platform.…”
supporting
confidence: 67%
“…These data suggest that ethanol may contribute to OESCC through aberrant gene methylation [61,62]. In addition, aberrant gene methylation may impact signaling pathways through critical pathway genes, such as Notch4 of the Notch signaling pathway [63], PTEN of the phospoinositide 3-kinase (PI3K)/Akt pathway [64], and Wnt inhibitory factor 1 (WIF1) of the Wnt signaling pathway [65]. Recent studies have also showed that aberrant methylation of histones and non-histone proteins also modulates multiple signaling pathways [66].…”
Section: Disturbance Of Systemic Metabolism Of Nutrientsmentioning
confidence: 99%
“…An association between CIMP and poor prognosis was also reported for patients with oral cancer, though CIMP was not an independent factor in predicting prognosis. 42 It might be worth addressing a potential link between the MS or MMSS with CIMP in larger cohorts of HNSCC patients for which genome-wide methylation data are available.…”
Section: Discussionmentioning
confidence: 99%